Análisis del valor histórico del edificio del ex hospital policlínico y propuesta urbana – arquitectónica - García Sánchez, Marjorie Alexandra (2023)
The street "Eugenio Espejo" in the city of Riobamba, is an axis of educational and commercial character due to its numerous facilities and has been selected for study because of the need to find a transversal connection in the city, which gave rise to a special interest in one of the facilities in its context, the current "Coordinación Zonal de Salud N°3" (Zonal Health Coordination N°3). This building is catalogued as a heritage building thanks to its history, however, at present it is devalued by its current function, so why is the building no longer valued by the population, being a building of historical and heritage character? The question and the search for an answer is the starting point of this work. To do so, we begin by contextualising the interest in the site of the current "Coordinación Zonal de Salud N°3", developing a historical biography of how the earthquake caused a before and after in the city of Riobamba, provoking a new resettlement and its particular extension over the course of time. To deepen the research , the first point is an in situ urban analysis of the context, which mainly details the components of urban space and the relationship of various relevant facilities with the study site, continuing with an architectural analysis that exposes the historical background and the evolutionary process of the state of the building according to the additions it has undergone over time, where the influence of republican and modern architectural styles can be observed. This culminates in an urban-architectural proposal whose main objective is the reconversion of the building and the creation of a new land use focused on the cultural role. The project proposal is mainly focused on the social, economic and cultural reintegration of the sector and the city, thanks to the implementation of a cultural centre that is implanted inan inclusive park of rehabilitation and slow pace, oriented to provide different and universal experiences, being in the same property with the Geriatric Hospital of the city, contemporary activities are linked in a subtle and permeable way, with extensive green areas and sensory routes, allowing to enhance the importance of the historical value of the building through the use given to it as a proposal, becoming a meeting point that promotes learning and art in allits branches.